Panel de control para la gestión de aplicaciones móviles de la ESPAM MFL - Loayza Zambrano, Jorge Roberto (2022)
The main objective of this degree work is to develop a web control panel for the management of mobile applications developed and to be developed at ESPAM MFL. To achieve the aforementioned objective, the agile development methodology Extreme Programming was used, which consists of four phases (planning, design, coding and testing), data collection was carried out through interviews with the main managers of the Software Development Unit to recognize the needs of each control panel module; subsequently, the design of the database and system interfaces was carried out, in the development phase an iterative and incremental process was proposed, providing small improvements to the project using tools such as ASP.NET Core 3.1 for the development of the backend, SQL server as manager database and Angular 8 in the development of the frontend, in the final phase of tests the corresponding verification of the correct operation of the control panel and integration with the Red Alumni mobile application was made. Through the results obtained, the optimization of time from planning to production of the changes that are required to be made in each of the registered mobile applications has been verified, allowing to manage its users, modules, content, files and personalized notifications, thus managing to maintain to the users of the applications always with the service in real time, which saves time and money, since application maintenance is no longer required with each update